Expressão gênica do mRNA FOSB, BDNF E DRD5 em sangue periférico de dependentes de álcool e crack-cocaína - Anders, Quézia (2019)
Chronic drug use has been associated with changes in gene expression in the brain, yielding long-term neural circuit changes resulting in compulsive behavior or craving. Evidence suggests that the drug may induce complex neuroadaptations after exposure and these changes are mediated by a dynamic pattern of gene regulation. It has been reported that changes in neural circuits begin after the first exposure, altering the expression of genes important for the state of dependence. We studied the gene expression of mRNA (messenger ribonucleic acid) FosB (Bcell homolog of murine osteosarcoma viral oncogene), BDNF (brain-derived neutrophic factor) and DRD5 (dopamine D5 receptor) in dependent patients hospitalized for clinical treatment. For molecular analysis, peripheral blood was collected in an anticoagulant tube, and the extraction of RNA from the lymphocytes did not exceed 2 hours after collection. RNA was used for the synthesis of cDNA (complementary deoxyribonucleic acid) which was amplified by PCR (real-time polymerase chain reaction) using the specific primer. There was a reduced FosB mRNA expression since the fold-change calculated was -1,15 in crack-cocaine dependents (CUD) and -2.17 in alcohol dependents (AUD) compared to non-dependent controls. The Hedge’s effect size gs of the Log FosB/Act was of 0.66 (medium effect size according to Cohen’s convention) the CUD and of 0.3 (small effect size) for the AUD. However, there was an increase in the expression of BDNF and DRD5 mRNAs in both CUD and AUD groups compared to controls. The fold-change of the BDNF mRNA expression for the CUD was 2.25 and 2.0 for the AUD, and the Hedge’s gs effect size of the Log BDNF/Act of 0.35 and 0.36 (small to medium effect size), respectively. The foldchange of DRD5 mRNA expression was 2.22 for both CUD and AUD groups, and the Hedge’s gs effect size of the Log DRD5/Act of 0.25 and 0.26 (small effect size), respectively. These data suggest that it is possible to detect changes in gene expression of central occurrence in lymphocytes present in the peripheral blood and these changes may reflect the molecular changes that occur in neural circuits in drug addiction.